2008
DOI: 10.1152/jn.01386.2007
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Heterogeneity of Cortical Receptive Fields and Its Impact on Multisensory Interactions

Abstract: Carriere BN, Royal DW, Wallace MT. Spatial heterogeneity of cortical receptive fields and its impact on multisensory interactions. J Neurophysiol 99: 2357-2368, 2008. First published February 20, 2008 doi:10.1152/jn.01386.2007. Investigations of multisensory processing at the level of the single neuron have illustrated the importance of the spatial and temporal relationship of the paired stimuli and their relative effectiveness in determining the product of the resultant interaction. Although these principles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 80 publications
6
36
1
Order By: Relevance
“…Finally, cross-sensory modulations may target subsets of neurons based on their response level, laminar location, and neuron type within each rearing condition. The fact that the auditory clicks failed to drive any barrel cortex neurons under any conditions in the present study indicates that the cross-sensory multisensory interactions observed here are modulatory in nature (Dehner et al, 2004;Lakatos et al, 2007;Carriere et al, 2008), as opposed to the directly driven responses found in association cortex (Wallace et al, 1992;Carriere et al, 2007), and may account for the difficulty in detecting multisensory influences in primary sensory cortex. Surprisingly, the modulatory influence is present even in normally reared rats and is maximally enhanced when whisker deprivation is coupled with click rearing.…”
Section: Discussioncontrasting
confidence: 47%
“…Finally, cross-sensory modulations may target subsets of neurons based on their response level, laminar location, and neuron type within each rearing condition. The fact that the auditory clicks failed to drive any barrel cortex neurons under any conditions in the present study indicates that the cross-sensory multisensory interactions observed here are modulatory in nature (Dehner et al, 2004;Lakatos et al, 2007;Carriere et al, 2008), as opposed to the directly driven responses found in association cortex (Wallace et al, 1992;Carriere et al, 2007), and may account for the difficulty in detecting multisensory influences in primary sensory cortex. Surprisingly, the modulatory influence is present even in normally reared rats and is maximally enhanced when whisker deprivation is coupled with click rearing.…”
Section: Discussioncontrasting
confidence: 47%
“…The innovative discovery is that the firing rate within individual receptive fields of neurons is heterogeneous and varies with stimulus effectiveness in spatially and temporally dependent manners (for review, see Krueger et al, 2009). Superadditive and subadditive hotspots are not stationary within the neuron's receptive field either in cortical (Carriere et al, 2008) or subcortical ) structures and furthermore are not straightforwardly predicted by unisensory response patterns. These features were further evident when data were analyzed at a population level, such that the percentage of integration was higher (in their population of neurons) along the horizontal meridian than for other positions, even though response profiles were uniformly distributed (Krueger et al, 2009).…”
Section: Synergistic Interplay Between Principles Of Multisensory Intmentioning
confidence: 96%
“…Parallel evidence at the single-neuron level similarly nuances how principles of multisensory interactions cooperate. Responses expressing multisensory interactions within subregions of a neuron's receptive field are heterogeneous and give rise to integrative "hot spots" (Carriere et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recent strides within this area have extended our understanding of the neural correlates of multisensory integration from the single cell to more distributed neural representations, have begun to provide evidence on the role of dynamic binding mechanisms in multisensory processing (e.g. Cappe et al, 2009Cappe et al, , 2012Carriere et al, 2008;Maier et al, 2008;Royal et al, 2009;Senkowski et al, 2007) and started to establish strong functional links between neural activity profiles and changes in behavior and perception (e.g. Murray et al, 2016).…”
Section: Introductionmentioning
confidence: 99%